On research libraries : statement and recommendations, submitted to National Advisory Commission on Libraries, Nov. 1967 - American Council of Learned Societies Devoted to Humanistic Studies; United States (Cambridge, Mass. : M.I.T. Press, 1969)
This report of statements and recommendations from the ACIS Committee on Research Libraries is useful to the person with little knowledge of functioning of research libraries, to the scholar, and to the research library user, for volume assesses the current deficiencies and weaknesses and strengths of the technical side of running research libraries as well as commenting on directions in which library functions must move as automation becomes ever more important. more important. The professional research librarian will also find helpful guidance here.
Includes index.
Includes bibliographical references: p. 100.
rpm 30/08/2018
Loans
Keywords: Research libraries